Dívida pública brasileira e seu mecanismo de contágio: uma análise empírica - Santos Junior, Antonio Germano dos (2005)
Since the beginning of the Real Plan, in July 1994, the ratio Public Debt/GDP had a vertiginous increase going from a level around 30% in the begin of the period to an amount above 57% at the end of 2002. From this moment onwards the ratio restarted a new decreasing path. During this period, Brazil has gone through some crisis in the internal field as well as in the external one which contributed to the aggravation of this relation. The goal of this work is to analyze the behavior of this relationship, which is considered one of the most important indices of a country’s solvency during a period of time. So, this research is divided into three different sub-analyses. The first aims to model the debt in the short term through the methodology of the minimum ordinary squares. The following analysis demonstrates the mechanism of infection of the public debt under the vision of vector autoregressions. And in the last one a model of debt dynamic is developed using difference equations from which the condition of solvency of a country can be obtained. From this point, several exercises of this variable path are tested. For the available sample and considering the three different analysis, the outcomes corroborate the presented theory. In such case, it is clear that the behavior’s study of the public debt is essential for a better understanding of some economic policies applied so far in Brazil.